A Public Relations Approach to Co-Creational Image Management in Professional Sport - Dottori, Michael Mark (Université d'Ottawa / University of Ottawa, 2018)
This dissertation investigated the influence of legitimacy and social media on organizational image management (IM) in North American professional sport. The author used a social theory approach to public relations in which legitimization is a core function, stakeholders influence the organization’s identity, and communicating identity is a legitimacy-seeking action that co-creationally drives organizational IM. This study examined the Ottawa Sport and Entertainment Group (OSEG), a conglomerate sport organization, using a qualitative embedded exploratory case study, which allowed analysis at different organizational levels, online and offline, using thematic and content analysis. The first two research questions explored the relationships between identity, image, and legitimacy in a social media world. The second two explored the explicit effects of social media on identity, legitimacy, image, and how these constructs manifest through social media. The first phase of the study used interview (N-52) and document (N-4) analyses to explore how identity, image, and legitimacy interact. Results showed that organizations’ legitimacy-seeking behaviour drives IM. The impetuous to change image comes from the outward facing legitimacy-seeking negotiation of image with external stakeholders. In phase two, using the legitimacy framework developed by Lock, Filo, Kunkel, and Skinner (2015), 5,668 tweets and retweets were coded, revealing 10 communicated image themes that sought technical, managerial, personal, and linkage legitimacy. These types of legitimacy were present in 99.5% of tweets and retweets. They sought to build trust, reinforce an image and identity of community involvement, and create conformity pressure. Such activities indirectly encouraged or legitimized expressions of fan support while inhibiting dissenting opinions. Previous research noted that identity and its expression through image are no longer defined solely by organizations. This study sought to extend image and identity research by suggesting legitimacy judgments drive co-creational identity and image change. The research extended Gioia, Hamilton, and Patvardhan’s (2014) process model of identity-image interdependence, creating a new framework for Twitter IM. The research explored how social media technology develops organizational identity, image, and legitimacy to provide insights necessary for fostering the effective use of IM and sport PR’s role within it.
Keywords: Public Relations; Sport; Image; Social Media